China and the Third World are not "catching up" to the rich countries. (18th December 2018) - King, Samuel T.
Abstract : Income data show there has been no convergence in prosperity or developmental levels between rich and poor states during the neoliberal period. Analysis of per capita income for every country between 1980 and 2015 reveals the widespread idea of a catch‐up by the so‐called "emerging market" economies, is not supported. Almost all states (98.6% by population) are either rich or poor, with 85% defined as poor. There has also been a widening of the income gap between these two poles. The rise of average Chinese income over the period to a level similar to other large relatively developed poor states such as Mexico and Brazil fits very much within this pattern of global polarization and does not challenge it. What appears to have "emerged" in China and some other regions is a new relative level of development among still poor states, not new rivals to the world's richest countries.